PENINGKATAN TARIF HIDUP LAYAK MELALUI PRODUKTIVITAS BEKERJA PERSPEKTIF AL-QUR'AN - Abd. Basid (UIN Sunan Kalijaga Yogyakarta, 2020)
The main problem of humans in the process of meeting their needs lies in their ability to improve a better standard of living. This problem is more rooted in human consciousness to encourage themselves to be more productive in living life. In the context of Islamic societies, the most effective way of encouraging them to improve their standard of living is by using religious argumentations, particularly the Qur'an. The Qur'an contains a set of rules that explain how a person can enhance his quality of life. By using the al-Farmawi thematic method and the hermeneutics of liberation, this study revealed that an improvement in work ethic is needed to improve a better standard of living. The enhancement of work ethic can be actualized when humans realize their self essences and the essence of God's creation. To gain the self essence is by raising awareness that God, through his generosity, has given each person livelihood since the beginning of creation. Humans' assignment is only to obtain the livelihood in the right ways. This belief makes them not to be ambitious in working while their self essences can awaken humans to be always proportional in their work and can understand the given rules. The basis of theological liberation in the Qur'an does not only take place in one broad social community but also in every individual through awareness of the meaning of various symbols given by God. This then can lead people to a more decent level of life applied to work productivity.